Surface doping modified lithium cobalt oxide material, preparation method and application in high-voltage lithium battery
By doping potassium, phosphorus and fluorine elements on the surface of lithium cobalt oxide material and adopting high-temperature annealing process, the problem of electrochemical performance decay of lithium cobalt oxide cathode material under high voltage fast charging conditions is solved, and the structural stability and electrochemical performance of the material are improved.
Patent Information
- Application Number
- CN202311184164.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-13
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2043-09-13
AI Technical Summary
The electrochemical performance of lithium cobalt oxide cathode material has severely declined under high voltage fast charging conditions, resulting in material polarization and irreversible phase change, thereby accelerating the deterioration of battery performance.
By doping potassium, phosphorus and fluorine elements on the surface of lithium cobalt oxide material, using specific raw material ratios and high-temperature annealing process, surface-doped modified lithium cobalt oxide materials were prepared.
The structural stability and electrochemical performance of lithium cobalt oxide cathode material at high voltages are significantly improved, the ionic conductivity and electronic conductivity of the material are enhanced, thereby improving the high voltage fast charging performance and cycling stability of the battery.
Smart Images

Figure CN119627094A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of battery materials, and in particular relates to a surface-doped and modified lithium cobalt oxide material, a preparation method thereof, and an application in a high-voltage lithium battery. Background Art
[0002] Lithium cobalt oxide cathode materials have the advantages of high compaction density, high volume energy density and long cycle life, and they play an important role in the portable electronic terminal equipment market such as computers, communications and consumer products. As electronic products develop towards diversification, thinness, high performance and intelligence, the battery market is in urgent need of small energy storage devices with high energy density and high power density.
[0003] Improving the fast charging performance and charging cut-off voltage of lithium cobalt oxide positive electrodes is an important way to improve the energy density and power density of lithium-ion batteries. However, with the increase of fast charging rate and charging cut-off voltage, the electrochemical performance of lithium cobalt oxide positive electrodes seriously declines. This is mainly because the side reactions at the interface between the positive electrode material and the electrolyte are intensified under high charging cut-off voltage, and the high degree of delithiation leads to irreversible phase change. The polarization of the material under fast charging leads to the intensification of surface side reactions and the production of irreversible phase change, which in turn accelerates the decline of the electrochemical performance of the lithium cobalt oxide positive electrode material.
[0004] Therefore, improving structural stability and reducing material polarization are the technical key points that need to be overcome to increase the fast charging performance and charging cut-off voltage of lithium cobalt oxide positive electrodes, and are also an important direction for the development of new advanced lithium-ion battery positive electrode materials in recent years. Summary of the invention
[0005] In view of this, the present invention provides a surface-doped modified lithium cobalt oxide material, a preparation method and an application in a high-voltage lithium battery. The main purpose is to solve the technical problem that the electrochemical performance of high-voltage fast-charging lithium cobalt oxide positive electrode materials needs to be improved.
[0006] On the one hand, the present invention provides a surface-doped modified lithium cobalt oxide material, wherein the surface-doped modified lithium cobalt oxide material is a lithium cobalt oxide material with potassium, phosphorus and fluorine doped on its surface.
[0007] Optionally, the surface doped and modified lithium cobalt oxide material has a reversible specific capacity of 200 to 230 mAh / g at a rate of 1C in a voltage range of 3.0 to 4.6 V, and a reversible specific capacity of 115 to 155 mAh / g at a rate of 50C.
[0008] Optionally, the reversible specific capacity of the surface doped and modified lithium cobalt oxide material at a rate of 1C is selected from any value among 200, 205, 210, 215, 220, 225, 230 mAh / g or a range value between any two of them.
[0009] Optionally, the reversible specific capacity of the surface doped and modified lithium cobalt oxide material at a rate of 50C is any value of 115, 120, 125, 130, 135, 140, 145, 150, 155 mAh / g or a range between any two of them.
[0010] In a second aspect, the present invention provides a method for preparing the above-mentioned surface-doped and modified lithium cobalt oxide material, the preparation method comprising the following steps:
[0011] S1: Obtain lithium cobalt oxide;
[0012] S2: mixing the raw materials containing the lithium cobalt oxide, potassium source, phosphorus source and fluorine source described in step S1 to obtain a precursor dry material;
[0013] S3: The precursor dry material in step S2 is heated in an air medium for I and kept warm for I to obtain the surface-doped and modified lithium cobalt oxide material.
[0014] Optionally, in step S2, the mass ratio of the lithium cobalt oxide, the potassium source, the phosphorus source and the fluorine source is 100: (0.0001-0.05): (0.0001-0.08): (0.0001-0.09).
[0015] Optionally, the mass ratio of the lithium cobalt oxide, the potassium source, the phosphorus source and the fluorine source is 100: (0.0005-0.05): (0.0005-0.08): (0.0005-0.09).
[0016] Optionally, the mass ratio of the lithium cobalt oxide, the potassium source, the phosphorus source and the fluorine source is 100: (0.001-0.05): (0.001-0.08): (0.001-0.09).
[0017] Optionally, the mass ratio of the lithium cobalt oxide, the potassium source, the phosphorus source and the fluorine source is 100: (0.005-0.05): (0.005-0.08): (0.005-0.09).
[0018] Optionally, the mass ratio of the lithium cobalt oxide, the potassium source, the phosphorus source and the fluorine source is 100: (0.01-0.05): (0.01-0.08): (0.01-0.09).
[0019] Optionally, the mass ratio of the lithium cobalt oxide, the potassium source, the phosphorus source and the fluorine source is 100: (0.01-0.04): (0.01-0.07): (0.01-0.08).
[0020] Optionally, the mass ratio of the lithium cobalt oxide, the potassium source, the phosphorus source and the fluorine source is 100: (0.01-0.03): (0.01-0.05): (0.01-0.06).
[0021] Optionally, the mass ratio of the lithium cobalt oxide, the potassium source, the phosphorus source and the fluorine source is 100: (0.02-0.03): (0.02-0.05): (0.02-0.06).
[0022] Another expression of the mass ratio of the lithium cobalt oxide, the potassium source, the phosphorus source and the fluorine source in the present invention is: 100:x:y:z, 0.01%≤x≤5%, 0.01%≤y≤8%, 0.01%≤y≤9%;
[0023] x is the mass percentage of the potassium source to 100 parts of lithium cobalt oxide;
[0024] y is the mass percentage of the phosphorus source to 100 parts of lithium cobalt oxide;
[0025] z is the mass percentage of the fluorine source to 100 parts of lithium cobalt oxide.
[0026] Optionally, x is selected from any value of 0.01%, 0.50%, 1.0%, 1.5%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, 5.0%, or any range therebetween.
[0027] Optionally, y is selected from any value among 0.01%, 0.50%, 1.0%, 1.5%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, 5.0%, 5.5%, 6.0%, 6.5%, 7.0%, 7.5%, 8.0% or any range therebetween.
[0028] Optionally, x is selected from any value among 0.01%, 0.50%, 1.0%, 1.5%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, 5.0%, 5.5%, 6.0%, 6.5%, 7.0%, 7.5%, 8.0%, 8.5%, 9%, or any range therebetween.
[0029] Optionally, in step S3, the temperature of the heating I is 600-1000° C., and the time of the insulation I is 2-12 hours.
[0030] Optionally, the temperature of the heating I is selected from any value of 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, 900°C, 950°C, 1000°C or any range therebetween.
[0031] Optionally, the insulation time I is selected from any value among 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12 hours or any range value between two of them.
[0032] Optionally, in step S2, the potassium source is selected from at least one of potassium carbonate, potassium bicarbonate, potassium chloride, potassium nitrate and potassium hexafluorophosphate.
[0033] Optionally, in step S2, the phosphorus source is selected from at least one of phosphoric acid, potassium dihydrogen phosphate, diammonium hydrogen phosphate, ammonium dihydrogen phosphate and potassium hexafluorophosphate.
[0034] Optionally, in step S2, the fluorine source is selected from at least one of calcium fluoride, sodium fluoride, potassium fluoride, ammonium fluoride and potassium hexafluorophosphate.
[0035] Optionally, in step S1, the lithium cobalt oxide is a product of mixing cobalt trioxide and a lithium source, heating II in an air medium, and keeping warm II; it is nano lithium cobalt oxide powder.
[0036] The unmodified lithium cobalt oxide in the present invention can also be obtained from the prior art.
[0037] Optionally, the atomic molar ratio of the cobalt oxide to the lithium source is 1:1 to 1.1; the temperature of the heating II is 600 to 1000° C.; and the time of the heat preservation II is 2 to 12 hours.
[0038] Optionally, the temperature of the heating II is selected from any value of 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, 900°C, 950°C, 1000°C or any range therebetween.
[0039] Optionally, the insulation II time is selected from any value among 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12 hours or any range value between two of them.
[0040] Optionally, the atomic molar ratio of the cobalt oxide to the lithium source is selected from any value of 1:1, 1:1.05, 1:1.1, or any range between the two.
[0041] Optionally, the cobalt oxide is a product of cobalt hydroxide heated to III and kept warm to III in an air medium; it is nano cobalt oxide powder.
[0042] The cobalt tetraoxide in the present invention can also be obtained from the prior art.
[0043] Optionally, the temperature of the heating III is 200-600° C., and the time of the insulation III is 2-6 hours.
[0044] Optionally, the temperature of the heating III is selected from any value of 200°C, 250°C, 300°C, 350°C, 400°C, 450°C, 500°C, 550°C, 600°C or any range therebetween.
[0045] Optionally, in step S3, the heating rate of the heating I is 5 to 20°C / min; the heating rate of the heating II is 2 to 20°C / min; and the heating rate of the heating III is 2 to 20°C / min.
[0046] Optionally, the cobalt hydroxide is a product of a cobalt salt and ammonia water heated at 600-100° C. and kept warm for 1-24 hours, and then centrifuged, washed, and freeze-dried to obtain nano cobalt hydroxide powder.
[0047] The cobalt hydroxide of the present invention can also be obtained from the prior art.
[0048] Optionally, the cobalt salt is selected from cobalt nitrate.
[0049] The present invention provides a specific method for preparing a surface-doped and modified high-voltage fast-charge lithium cobalt oxide positive electrode material, the method comprising the following steps:
[0050] S1. Preparation of nano lithium cobaltate powder: Weigh 10-50g polyvinyl pyrrolidone and 1-20g cobalt nitrate hexahydrate and disperse them in 0.5-1.0L deionized water, and heat them in an oil bath to 60-100°C; add 5-30mL of 25% ammonia water to the above solution, keep warm and stir, the stirring speed is 100-1000rmp, and the insulation time is 1-24h; centrifuge and wash the above reaction product, ultrasonically disperse and freeze-dry to obtain nano cobalt hydroxide powder, the centrifugal speed is 4000-10000r / min. Take the above cobalt hydroxide powder and place it in a muffle furnace, heat and keep it in air medium, the heating rate is 5-20℃ / min, the temperature is 200-600℃, and the insulation time is 2-6h. After natural cooling, nano cobalt trioxide powder is obtained.
[0051] Cobalt trioxide and a lithium source were weighed according to an atomic molar ratio of 1:1.05, mixed and ground to obtain a precursor dry material.
[0052] The above-mentioned dry precursor is placed in a muffle furnace, and heated and kept warm in air medium, 5-20℃ / min, temperature is 600-1000℃, and the holding time is 2-12h. After the process is completed, the product is taken out to obtain nano lithium cobalt oxide powder.
[0053] S2. Prepare surface-doped lithium cobalt oxide positive electrode material: according to the mass ratio of 100:x:y:z, wherein: 0.01%≤x≤5%, 0.01%≤y≤8%, 0.01%≤y≤9%; (x is the mass percentage of the potassium source to 100 parts of lithium cobalt oxide; y is the mass percentage of the phosphorus source to 100 parts of lithium cobalt oxide; z is the mass percentage of the fluorine source to 100 parts of lithium cobalt oxide), weigh lithium cobalt oxide, potassium source, phosphorus source, and fluorine source, mix and grind to obtain a precursor dry material.
[0054] The above-mentioned dry precursor material is placed in a muffle furnace, heated and kept warm in air medium, 5-20℃ / min, temperature is 600-1000℃, and the holding time is 2-12h. After the heating process is completed, the product is taken out and quenched in air to obtain a surface-doped lithium cobalt oxide positive electrode material.
[0055] Optionally, the polyvinyl pyrrolidone in S1 is one or more of PVP-K12, PVP-K15, PVP-K17, PVP-K25, PVP-K30, PVP-K60, and PVP-K90.
[0056] In a third aspect, the present invention provides a lithium cobalt oxide positive electrode component, comprising a conductive substrate and a slurry coated on the surface of the conductive substrate; the raw material of the slurry comprises the above-mentioned surface-doped and modified lithium cobalt oxide material.
[0057] Optionally, the preparation method of the lithium cobalt oxide positive electrode component is as follows: the lithium cobalt oxide material is mixed with conductive carbon black and polyvinylidene fluoride adhesive in a mass ratio of (6-10):1:1 and ground, and then an appropriate amount of solvent is added to form a slurry; the slurry is evenly scraped on a carbon-coated aluminum foil, and the positive electrode sheet is obtained after drying.
[0058] In a fourth aspect, the present invention provides a high-voltage fast-charging lithium-ion battery, comprising a positive electrode component, a negative electrode component, a separator, and an electrolyte; the positive electrode component is the above-mentioned lithium cobalt oxide positive electrode component.
[0059] Optionally, the negative electrode is a metal lithium sheet, the separator is a Celgard2400 membrane, and the electrolyte is a LB-372 high-voltage electrolyte.
[0060] Optionally, the battery is a CR2016 button battery.
[0061] In a fifth aspect, the present invention provides the use of the above-mentioned surface-doped and modified lithium cobalt oxide material in a high-voltage ultra-fast charging lithium-ion battery.
[0062] Compared with the prior art, the present invention has the following beneficial effects:
[0063] 1) The lithium cobalt oxide positive electrode material suitable for high voltage fast charging prepared by the present invention is modified by surface doping with multiple elements such as potassium, phosphorus and fluorine. By optimizing the raw materials, doping content and preparation process, not only the reversibility of the bulk crystal structure and the surface structural stability of the material under high voltage are improved, but also the ionic conductivity and electronic conductivity of the material are improved, thereby achieving the improvement of the high voltage ultra-fast charging performance and cycle stability of the lithium cobalt oxide positive electrode material.
[0064] 2) The preparation method provided by the present invention has good controllability, is simple and easy to operate, and is suitable for expanding production and realizing industrialization. BRIEF DESCRIPTION OF THE DRAWINGS
[0065] Figure 1 This is a scanning electron microscope image of the potassium / phosphorus / fluorine surface-doped modified lithium cobalt oxide positive electrode material prepared in Example 1 of the present invention;
[0066] Figure 2 This is a scanning electron microscope image of the unmodified lithium cobalt oxide positive electrode material prepared in Comparative Example 1 of the present invention;
[0067] Figure 3 This is a rate performance test graph of a lithium ion battery assembled with a potassium / phosphorus / fluorine surface-doped modified lithium cobalt oxide positive electrode material of Example 1 of the present invention and an unmodified lithium cobalt oxide positive electrode material of Comparative Example 1 at a constant temperature of 28° C. in a voltage range of 3.0-4.6V;
[0068] Figure 4 The charge and discharge curves of a lithium-ion battery assembled with the potassium / phosphorus / fluorine surface-doped modified lithium cobalt oxide positive electrode material prepared in Example 1 of the present invention at different rates in the voltage range of 3.0-4.6V at a constant temperature of 28°C;
[0069] Figure 5 A test graph of the cycling performance of a lithium-ion battery assembled with the potassium / phosphorus / fluorine surface-doped modified lithium cobalt oxide positive electrode material prepared in Example 1 of the present invention at a constant temperature of 28° C., in the voltage range of 3.0-4.6V, and at a rate of 1C. DETAILED DESCRIPTION
[0070] The present application is further described below in conjunction with specific embodiments. The following are only a few embodiments of the present application, and are not intended to limit the present application in any form. Although the present application discloses the following preferred embodiments, they are not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the above disclosed technical content to make some changes or modifications are equivalent to equivalent implementation cases and are within the scope of the technical solution.
[0071] Unless otherwise specified, the raw materials in the examples of the present application were purchased from commercial sources and used directly without any special treatment.
[0072] Unless otherwise specified, the analysis methods in the examples all adopt conventional settings and conventional analysis methods of instruments or equipment.
[0073] Example 1 (doped lithium cobalt oxide positive electrode material)
[0074] 10 g of polyvinyl pyrrolidone and 15 g of cobalt nitrate hexahydrate were dispersed in 1 L of deionized water and heated to 60° C. in an oil bath; 10 mL of 25% ammonia water was added to the solution, and the solution was kept warm and stirred at a stirring speed of 400 rmp for 2 h; the reaction product was centrifugally washed, ultrasonically dispersed and freeze-dried to obtain nano cobalt hydroxide powder at a centrifugal speed of 6000 r / min.
[0075] The cobalt hydroxide powder is placed in a muffle furnace and heated in an air medium at a heating rate of 5°C / min, a temperature of 400°C, and a holding time of 2h. After the temperature is naturally lowered, nano-cobalt trioxide powder is obtained.
[0076] According to the molar ratio of cobalt atoms to lithium atoms of 1:1.05, cobalt trioxide and lithium carbonate are weighed, mixed and ground to obtain a precursor dry material. The above precursor dry material is placed in a muffle furnace, heated and kept warm in an air medium, 5-20℃ / min, the temperature is 700℃, and the insulation time is 6h. After the procedure is completed, the product is taken out to obtain nano-lithium cobalt oxide powder.
[0077] Lithium cobalt oxide, potassium carbonate, ammonium dihydrogen phosphate, and ammonium fluoride were weighed in a mass ratio of 1:0.01:0.02:0.02, mixed and ground to obtain a precursor dry material.
[0078] The above-mentioned dry precursor material is placed in a muffle furnace and heated in an air medium at 5°C / min, a temperature of 800°C, and a holding time of 4 hours. After the heating process is completed, the product is taken out to obtain a surface-doped lithium cobalt oxide positive electrode material.
[0079] Example 2 (doped lithium cobalt oxide positive electrode material)
[0080] 20 g of polyvinyl pyrrolidone and 30 g of cobalt nitrate hexahydrate were dispersed in 1 L of deionized water and heated to 60° C. in an oil bath; 15 mL of 25% ammonia water was added to the solution, and the solution was kept warm and stirred at a stirring speed of 400 rmp for 2 h; the reaction product was centrifugally washed, ultrasonically dispersed and freeze-dried to obtain nano cobalt hydroxide powder at a centrifugal speed of 6000 r / min.
[0081] The cobalt hydroxide powder is placed in a muffle furnace and heated in an air medium at a heating rate of 5°C / min, a temperature of 400°C, and a holding time of 2h. After the temperature is naturally lowered, nano-cobalt trioxide powder is obtained.
[0082] According to the molar ratio of cobalt atoms to lithium atoms of 1:1.05, cobalt trioxide and lithium carbonate are weighed, mixed and ground to obtain a precursor dry material. The above precursor dry material is placed in a muffle furnace, heated and kept warm in an air medium, 5-20℃ / min, the temperature is 700℃, and the insulation time is 6h. After the procedure is completed, the product is taken out to obtain nano-lithium cobalt oxide powder.
[0083] Lithium cobalt oxide and potassium hexafluorophosphate were weighed at a mass ratio of 1:0.02, mixed and ground to obtain a precursor dry material.
[0084] The above-mentioned dry precursor material is placed in a muffle furnace and heated in an air medium at 5°C / min, a temperature of 900°C, and a holding time of 8 hours. After the heating process is completed, the product is taken out to obtain a surface-doped lithium cobalt oxide positive electrode material.
[0085] Example 3 (doped lithium cobalt oxide positive electrode material)
[0086] 20 g of polyvinyl pyrrolidone and 30 g of cobalt nitrate hexahydrate were dispersed in 1 L of deionized water and heated to 60° C. in an oil bath; 15 mL of 25% ammonia water was added to the solution, and the solution was kept warm and stirred at a stirring speed of 400 rmp for 2 h; the reaction product was centrifugally washed, ultrasonically dispersed and freeze-dried to obtain nano cobalt hydroxide powder at a centrifugal speed of 6000 r / min.
[0087] The cobalt hydroxide powder is placed in a muffle furnace and heated in an air medium at a heating rate of 5°C / min, a temperature of 400°C, and a holding time of 2h. After the temperature is naturally lowered, nano-cobalt trioxide powder is obtained.
[0088] According to the molar ratio of cobalt atoms to lithium atoms of 1:1.05, cobalt trioxide and lithium carbonate are weighed, mixed and ground to obtain a precursor dry material. The above precursor dry material is placed in a muffle furnace, heated and kept warm in an air medium, 5-20℃ / min, the temperature is 700℃, and the insulation time is 6h. After the procedure is completed, the product is taken out to obtain nano-lithium cobalt oxide powder.
[0089] Lithium cobalt oxide, potassium carbonate, ammonium dihydrogen phosphate, and ammonium fluoride were weighed in a mass ratio of 1:0.01:0.02:0.02, mixed and ground to obtain a precursor dry material.
[0090] The above-mentioned dry precursor material is placed in a muffle furnace and heated in an air medium at 5°C / min, a temperature of 700°C, and a holding time of 4 hours. After the heating process is completed, the product is taken out to obtain a surface-doped lithium cobalt oxide positive electrode material.
[0091] Example 4 (doped lithium cobalt oxide positive electrode material)
[0092] 20 g of polyvinyl pyrrolidone and 30 g of cobalt nitrate hexahydrate were dispersed in 1 L of deionized water and heated to 60° C. in an oil bath; 15 mL of 25% ammonia water was added to the solution, and the solution was kept warm and stirred at a stirring speed of 400 rmp for 2 h; the reaction product was centrifugally washed, ultrasonically dispersed and freeze-dried to obtain nano cobalt hydroxide powder at a centrifugal speed of 6000 r / min.
[0093] The cobalt hydroxide powder is placed in a muffle furnace and heated in an air medium at a heating rate of 5°C / min, a temperature of 400°C, and a holding time of 2h. After the temperature is naturally lowered, nano-cobalt trioxide powder is obtained.
[0094] According to the molar ratio of cobalt atoms to lithium atoms of 1:1.05, cobalt trioxide and lithium carbonate are weighed, mixed and ground to obtain a precursor dry material. The above precursor dry material is placed in a muffle furnace, heated and kept warm in an air medium, 5-20℃ / min, the temperature is 700℃, and the insulation time is 6h. After the procedure is completed, the product is taken out to obtain nano-lithium cobalt oxide powder.
[0095] Lithium cobalt oxide, potassium carbonate, ammonium dihydrogen phosphate, and ammonium fluoride were weighed in a mass ratio of 1:0.01:0.01:0.01, mixed and ground to obtain a precursor dry material.
[0096] The above-mentioned dry precursor material is placed in a muffle furnace and heated in an air medium at 5°C / min, a temperature of 800°C, and a holding time of 4 hours. After the heating process is completed, the product is taken out to obtain a surface-doped lithium cobalt oxide positive electrode material.
[0097] Comparative Example 1 (Undoped LiCoO2 Positive Electrode Material)
[0098] Weigh 20g polyvinyl pyrrolidone and 5g cobalt nitrate hexahydrate and disperse them in 1.0L deionized water, and heat them in an oil bath to 80°C. Add 15mL of 25% ammonia water to the above solution, keep warm and stir at a stirring speed of 400rmp for 1h. Wash the above reaction product by centrifugation, ultrasonically disperse and freeze-dry to obtain nano cobalt hydroxide powder.
[0099] The cobalt hydroxide powder is placed in a muffle furnace and heated in an air medium at a heating rate of 5°C / min, a temperature of 450°C, and a holding time of 2 hours. After the temperature is naturally lowered, nano-cobalt trioxide powder is obtained.
[0100] According to the molar ratio of cobalt atoms to lithium atoms of 1:1.05, cobalt trioxide and lithium carbonate are weighed, mixed and ground to obtain a precursor dry material. The precursor dry material is placed in a muffle furnace and heated and kept warm in an air medium at 5°C / min, the temperature is 800°C, and the holding time is 3h. After the heating process is completed, the product is taken out to obtain a lithium cobalt oxide positive electrode material.
[0101] Example 5 (lithium ion battery)
[0102] The lithium cobalt oxide positive electrode materials prepared in Examples 1 to 4 and Comparative Example 1 were weighed with conductive carbon black and polyvinylidene fluoride binder in a mass ratio of 8:1:1, mixed and ground, and then an appropriate amount of N-methylpyrrolidone was added dropwise, and grinding was continued until a uniform slurry was formed. The slurry was evenly scraped on the carbon-coated aluminum foil and transferred to a vacuum oven at 100°C. After being completely dried, the aluminum foil was cut into positive electrode sheets with a diameter of 12 mm for standby use, and 5 different positive electrode sheets were obtained.
[0103] Using metallic lithium sheet as negative electrode, Celgard2400 membrane as separator, and LB-372 high-voltage electrolyte provided by Duoduo Reagent Co., Ltd., CR2016 button cells were assembled in a glove box protected by argon atmosphere to obtain 5 different lithium-ion batteries.
[0104] The evaluation method of the electrochemical performance of the lithium cobalt oxide positive electrode material of the present invention is as follows:
[0105] The above five lithium-ion batteries were placed in a constant temperature box at 28°C and subjected to rate and cycle charge and discharge tests within the voltage window of 3.0-4.6V. Figure 3 The corresponding charge and discharge curves at different rates are shown in Figure 4 shown.
[0106] Correspondingly, the potassium / phosphorus / fluorine surface-doped modified lithium cobalt oxide positive electrode material prepared in Examples 1 to 4 of the present invention has a reversible specific capacity of 226.4 mAh / g at a rate of 1C; at a rate of 50C, the reversible specific capacity is 136.2 mAh / g, and the capacity retention rate is 60%.
[0107] The undoped lithium cobalt oxide positive electrode material prepared in Comparative Example 1 has a reversible specific capacity of 167.3 mAh / g at 1C and a reversible specific capacity of 23.6 mAh / g at 50C, and the corresponding capacity retention rate is only 14%.
[0108] By comparison, it can be seen that the reversible specific capacity of the positive electrode material prepared in Comparative Example 1 is significantly lower than that of the potassium / phosphorus / fluorine surface doped modified lithium cobalt oxide positive electrode material prepared in the present invention; specifically, the reversible specific capacity of the potassium / phosphorus / fluorine surface doped modified lithium cobalt oxide positive electrode material of the present invention at a rate of 1C is 226.4 mAh / g, and that of Comparative Example 1 is 167.3 mAh / g, which is 1.35 times that of Comparative Example 1; the reversible specific capacity of the present invention at a rate of 50C is 136.2 mAh / g, and that of Comparative Example 1 is 23.6 mAh / g, which is more than 5 times that of Comparative Example 1, and the electrical properties of the doped lithium cobalt oxide positive electrode material of the present invention are significantly improved.
[0109] The above results show that the present invention can effectively improve the rate performance and reversible specific capacity of the material by surface doping the lithium cobalt oxide positive electrode material.
[0110] The present invention first adopts a liquid phase method and high temperature annealing to prepare nano lithium cobalt oxide powder. On this basis, the nano lithium cobalt oxide powder and the doping elements are evenly mixed according to a certain atomic ratio and subjected to high temperature annealing treatment. The present invention greatly improves the bulk structural stability of the lithium cobalt oxide positive electrode material, suppresses the side reaction of the interface between particles and the electrolyte under high voltage, and greatly improves the ionic conductivity and electronic conductivity of the lithium cobalt oxide positive electrode material. Thereby, the high voltage fast charging performance and high voltage cycle stability of the lithium cobalt oxide positive electrode material are improved. The preparation method provided by the present invention has good controllability, is simple and easy to operate, and is suitable for expanding production and realizing industrialization.
[0111] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.
Claims
1. A surface-doped and modified lithium cobalt oxide material, characterized in that: The surface doped and modified lithium cobalt oxide material is a lithium cobalt oxide material whose surface is doped with potassium, phosphorus and fluorine.
2. The surface-doped and modified lithium cobalt oxide material according to claim 1, characterized in that: The surface doped and modified lithium cobalt oxide material has a reversible specific capacity of 200 to 230 mAh / g at a rate of 1C in a voltage range of 3.0 to 4.6 V, and a reversible specific capacity of 115 to 155 mAh / g at a rate of 50C.
3. The method for preparing the surface-doped modified lithium cobalt oxide material according to claim 1 or 2, characterized in that: The preparation method comprises the following steps: S1: Obtain lithium cobalt oxide; S2: mixing the raw materials containing the lithium cobalt oxide, potassium source, phosphorus source and fluorine source described in step S1 to obtain a precursor dry material; S3: The precursor dry material in step S2 is heated in an air medium for I and kept warm for I to obtain the surface-doped and modified lithium cobalt oxide material.
4. The method for preparing the surface-doped modified lithium cobalt oxide material according to claim 3, characterized in that: In step S2, the mass ratio of the lithium cobalt oxide, the potassium source, the phosphorus source and the fluorine source is 100: (0.0001-0.05): (0.0001-0.08): (0.0001-0.09).
5. The method for preparing the surface-doped modified lithium cobalt oxide material according to claim 3, characterized in that: In step S3, the temperature of the heating I is 600-1000° C., and the time of the insulation I is 2-12 hours; Preferably, in step S2, the potassium source is selected from at least one of potassium carbonate, potassium bicarbonate, potassium chloride, potassium nitrate and potassium hexafluorophosphate; Preferably, in step S2, the phosphorus source is selected from at least one of phosphoric acid, potassium dihydrogen phosphate, diammonium hydrogen phosphate, ammonium dihydrogen phosphate and potassium hexafluorophosphate; Preferably, in step S2, the fluorine source is selected from at least one of calcium fluoride, sodium fluoride, potassium fluoride, ammonium fluoride and potassium hexafluorophosphate.
6. The method for preparing the surface-doped modified lithium cobalt oxide material according to claim 3, characterized in that: In step S1, the lithium cobalt oxide is a product of mixing cobalt trioxide and a lithium source, heating II in an air medium, and keeping II; Preferably, the atomic molar ratio of the cobalt oxide to the lithium source is 1:1 to 1.1; the temperature of the heating II is 600 to 1000° C.; the time of the heat preservation II is 2 to 12 hours; Preferably, the cobalt trioxide is the product of cobalt hydroxide being heated III and kept warm III in an air medium; wherein the temperature of the heating III is 200 to 600° C., and the time of keeping warm III is 2 to 6 hours; Preferably, in step S3, the heating rate of heating I is 5 to 20°C / min; the heating rate of heating II is 2 to 20°C / min; and the heating rate of heating III is 2 to 20°C / min.
7. A lithium cobalt oxide positive electrode component, comprising a conductive substrate and a slurry coated on the surface of the conductive substrate; characterized in that: The raw material of the slurry includes the surface-doped and modified lithium cobalt oxide material according to claim 1 or 2.
8. A high voltage fast charging lithium ion battery, comprising a positive electrode, a negative electrode, a separator, and an electrolyte; characterized in that: The positive electrode component is the lithium cobalt oxide positive electrode component as claimed in claim 7.
9. A high voltage fast charging lithium ion battery according to claim 8, characterized in that: The negative electrode is a metal lithium sheet, the separator is a Celgard2400 membrane, the electrolyte is a LB-372 high-voltage electrolyte; and the battery is a CR2016 button battery.
10. Use of the surface-doped and modified lithium cobalt oxide material according to claim 1 or 2 in a high-voltage ultrafast-charged lithium-ion battery.
Citation Information
Patent Citations
In-situ surface-modified lithium-rich material and preparation method thereof
CN106602024A
Preparation method of high-performance aluminum and potassium co-doped sodium vanadium fluorophosphates / carbon composite material
CN108417792A
High-voltage, high-energy and long-cycle-life lithium cobalt oxide cathode material and preparation method thereof
CN110010887A
Surface doping modification method of lithium cobalt oxide anode material
CN110061196A
Fluorine-modified high-voltage lithium cobalt oxide, preparation method and battery thereof
CN110817972A
Cited By
Cobaltosic oxide containing oxygen vacancy, preparation method, lithium cobalt oxide and lithium ion battery
CN122324869A
